Eliminating VEGFA+ tumor-associated neutrophils by antibody-drug conjugates boosts antitumor immunity and potentiates PD-1 immunotherapy in preclinical models of cervical cancer - Shili Yao; Lu Sun; Ye Lu; Xiu Zhu; Rui Xu; Tong Yang; Huarong Tang; Peng Guo; Tao Zhu (Cell Death and Disease)
Abstract Tumor-associated neutrophils (TANs) actively interact with antibody-drug conjugates (ADCs) within the tumor microenvironment (TME), though the detailed mechanisms governing their response to ADC treatment remain to be fully elucidated. Herein, we explored how ICAM1-targeted ADCs affect TAN dynamics in preclinical models of cervical cancer. We discovered that I-DXd, our in-house ADC targeting cervical cancer, effectively eliminates tumor cells through specific antigen recognition while concurrently depleting pro-tumor VEGFA + TANs via Fcγ receptor-mediated phagocytosis. This dual action promotes an immunologically favorable TME. Through comprehensive preclinical studies, we established a foundational understanding of the synergistic benefits of combining I-DXd treatment with PD-1 immune checkpoint inhibition, thereby opening new avenues for therapeutic intervention in advanced cervical cancer.